Non-conventional expression systems for the production of vaccine proteins and immunotherapeutic molecules - Isabelle Legastelois; Sophie Buffin; Isabelle Peubez; Charlotte Mignon; Régis Sodoyer; Bettina Werle (Taylor & Francis Group, 2017)
The increasing demand for recombinant vaccine antigens or immunotherapeutic molecules calls into question the universality of current protein expression systems. Vaccine production can require relatively low amounts of expressed materials, but represents an extremely diverse category consisting of different target antigens with marked structural differences. In contrast, monoclonal antibodies, by definition share key molecular characteristics and require a production system capable of very large outputs, which drives the quest for highly efficient and cost-effective systems. In discussing expression systems, the primary assumption is that a universal production platform for vaccines and immunotherapeutics will unlikely exist. This review provides an overview of the evolution of traditional expression systems, including mammalian cells, yeast and E.coli, but also alternative systems such as other bacteria than E. coli, transgenic animals, insect cells, plants and microalgae, Tetrahymena thermophila, Leishmania tarentolae, filamentous fungi, cell free systems, and the incorporation of non-natural amino acids.